Notulae ad floram Sloveniae - Praprotnik, Nada (Hladnikia (Ljubljana), 1998)
New localities in Slovenia
Keywords: fitogeografija; flora; florae; phytogeography; Slovenia; Slovenija; vegetacija; vegetation